Physico-chemical characterisation of Capparis scabrida seed oil and pulp, a potential source of eicosapentaenoic acid. (August 2020) - Abreu-Naranjo, Reinier; Ramirez-Huila, Wagner Nolasco; Reyes Mera, Jorge Julio; Banguera, Derwin Viafara; León-Camacho, Manuel
Abstract: The main nutraceutical properties were determined for Capparis scabrida fruit seed oil to evaluate the potential of this species as an unconventional source of plant oil. Nutritional properties were compared with commercial edible oils. The fatty acid composition was determined using gas chromatography analysis. The total phenolic content (TPC) and antioxidant activity were determined using the Folin-Ciocalteu method and using radical scavenging activity: 1, 1-diphenyl-2- picrylhydrazyl (DPPH) and 2, 2′-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid (ABTS) assays, respectively. The statistical tools of cluster and discriminant analysis were used to classify C. scabrida seed oil in comparison with other seed oils. The C. scabrida seed has 31.5% lipid, of which 52.8% is oleic acid. Eicosapentaenoic acid, which is uncommon in the plant kingdom, was found. The omega-6 (7.87%):omega-3 (2.97%) ratio was 2.7:1, which is consistent with recent dietary guidelines. The TPC, DPPH and ABTS value were 150 mg gallic acid equivalents kg −1, 1.11 and 1.94 mM Trolox kg −1, respectively, for C. scabrida seed oil. Highlights: C.scabrida seed oil showed an unusual fatty acid composition. Capparis scabrida seed oil is a vegetable source of eicosapentaenoic acid. C.scabrida has a ω-6:ω-3 ratio, consistent with current dietary recommendations.